Molecular detection of Chlamydia Trachomatis and Mycoplasma Hominis in endometriosis lesions - F. Azizvakili; G. Saadatnia; P. Salehian; N. Bakhtiari; S. Rezaei (The Journal of Qazvin University of Medical Sciences, 2016)
Background: Retrograde of menstrual blood into the peritoneal cavity is one of the accepted theories for initiation of endometriosis although indicated that other factors are involved in pathogenesis. Investigation of infectious agents is important in this regard. Objective: To investigate the presence of bacterial infections; Chlamydia trachomatis and Mycoplasma Hominis as risk factors in endometriosis lesions. Methods: This case-control study was conducted in Sarem Hospital in 2014. DNA was extracted from 90 paraffin-embedded blocks included 40 endometriosis tissue samples, 23 samples of endometrial tissue from the same patients and 27 samples of endometrial tissue of the patients without endometriosis, and molecular analysis were performed using polymerase chain reaction. Results were analyzed by Fisher Exact Test and McNemar Test. Findings: Chlamydia trachomatis infection was seen in 11 (27.5%) endometriosis tissue, 3 (13%) normal tissue from patients and 10 (37%) in patient without endometriosis. Mycoplasma hominis was diagnosed in 11 (27.5%) endometriosis tissue, 7 (30.4%) of normal tissue from patients and one patient without endometriosis (3.7%). These differences show significant relations between infection with Mycoplasma hominis and endometriosis. Conclusion: The findings of this study did not show significant association between Chlamydia trachomatis infections and endometriosis. However; it seems Mycoplasma hominis infection can increase the risk of endometriosis incidence.